2011
DOI: 10.1371/journal.pone.0018936
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cancer Aggressive Features in Melanoma Cells by MicroRNAs

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs with regulatory roles, which are involved in a broad spectrum of physiological and pathological processes, including cancer. A common strategy for identification of miRNAs involved in cell transformation is to compare malignant cells to normal cells. Here we focus on identification of miRNAs that regulate the aggressive phenotype of melanoma cells. To avoid differences due to genetic background, a comparative high-throughput miRNA profiling was performed on two isog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 50 publications
2
68
0
Order By: Relevance
“…miR-185 was found to suppress glioma cell invasion, indicating that it may be a potential prognostic marker and therapeutic target (16). Previous studies have revealed that miR-185 impedes anchorage-independent growth, cell migration and invasion, in addition to suppressing tumor growth in vivo and increasing cisplatin sensitivity by promoting apoptosis, implicating it as a potent tumor suppressor (17)(18)(19). In the present study, overexpression of miR-185 repressed the growth and invasion of colon cancer cells in vitro and in vivo, which was consistent with the results of previous studies, indicating that miR-185 is a negative regulator of RhoA and Cdc42 and their cellular activities, and can inhibit the proliferation and invasion of CRC cells (20).…”
Section: Discussionmentioning
confidence: 99%
“…miR-185 was found to suppress glioma cell invasion, indicating that it may be a potential prognostic marker and therapeutic target (16). Previous studies have revealed that miR-185 impedes anchorage-independent growth, cell migration and invasion, in addition to suppressing tumor growth in vivo and increasing cisplatin sensitivity by promoting apoptosis, implicating it as a potent tumor suppressor (17)(18)(19). In the present study, overexpression of miR-185 repressed the growth and invasion of colon cancer cells in vitro and in vivo, which was consistent with the results of previous studies, indicating that miR-185 is a negative regulator of RhoA and Cdc42 and their cellular activities, and can inhibit the proliferation and invasion of CRC cells (20).…”
Section: Discussionmentioning
confidence: 99%
“…Net proliferation was determined by standardized XTT colorimetric assay (Biological Industries) as previously described (26).…”
Section: Net Proliferation Assaymentioning
confidence: 99%
“…miR-31 is reported to have tumor-suppressing functions, and its expression is decreased during tumorigenesis in several types of cancer, including breast, ovarian, prostate, bladder, hepatocellular, and gastric carcinoma and melanoma (9)(10)(11)(12)(13)(14)(15)(16). In contrast, a proproliferative function for miR-31 was reported in colorectal, head and neck squamous cell, small-cell lung, and esophageal squamous cell carcinoma (13,(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%